Density and Diversity of Zooplankton in Palu Bay after the Tsunami Disaster 28 September 2018 - Ritman Ishak Paudi; Manap Trianto (Jurnal Biologi Tropis, 2021)
One of the marine areas in Central Sulawesi is Palu Bay. Research on the Density and Diversity of Zooplankton Species in the Palu Bay area of Central Sulawesi after the Tsunami Disaster 28 September 2018. This study aims to determine: Density and Diversity Index of Zooplankton Species. Sampling is carried out at the beginning of the month by considering the state of the neighbours, namely the transition between the first and second full tides when the tidal currents are weak. The research design used a completely randomized design model with seasons, stations, and depths as treatments. Community analysis based on species identification, number of individuals, density, diversity index,. The results showed that the composition of the zooplankton community in the Palu bay area after the Tsunami Disaster of 28 September 2018 consisted of 23 types of zooplankton, which were dominated by: the Copepoda group. The values of the Density and Diversity Index are influenced by habitat, time, and sea depth. The conclusion is that habitat or station, season, and depth are the 3 main factors that affect the density and diversity of zooplankton taxon species in the Palu Bay area.